2003
DOI: 10.2165/00003088-200342010-00001
|View full text |Cite
|
Sign up to set email alerts
|

Role of Variability in Explaining Ethanol Pharmacokinetics

Abstract: Variability in the rate and extent of absorption, distribution and elimination of ethanol has important ramifications in clinical and legal medicine. The speed of absorption of ethanol from the gut depends on time of day, drinking pattern, dosage form, concentration of ethanol in the beverage, and particularly the fed or fasting state of the individual. During the absorption phase, a concentration gradient exists between the stomach, portal vein and the peripheral venous circulation. First-pass metabolism and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
192
1
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(204 citation statements)
references
References 165 publications
8
192
1
3
Order By: Relevance
“…Several researchers have used similar clinical studies to investigate the absorption, distribution, metabolism, and elimination ͑collectively referred to as pharmacokinetics͒ of alcohol in the body by measuring alcohol concentrations in different compartments of the body ͑typically via blood and breath assays͒. [6][7][8][9] These studies have demonstrated that differences in alcohol concentration exist between different bodily fluids, including venous and arterial blood. This work, to our knowledge, provides the first comparison of forearm tissue alcohol to breath, venous, and capillary blood alcohol under similar conditions.…”
Section: Alcohol Testing In Societymentioning
confidence: 99%
See 1 more Smart Citation
“…Several researchers have used similar clinical studies to investigate the absorption, distribution, metabolism, and elimination ͑collectively referred to as pharmacokinetics͒ of alcohol in the body by measuring alcohol concentrations in different compartments of the body ͑typically via blood and breath assays͒. [6][7][8][9] These studies have demonstrated that differences in alcohol concentration exist between different bodily fluids, including venous and arterial blood. This work, to our knowledge, provides the first comparison of forearm tissue alcohol to breath, venous, and capillary blood alcohol under similar conditions.…”
Section: Alcohol Testing In Societymentioning
confidence: 99%
“…Thus, the objective of the nonlinear regression was to determine the value of k 12 that minimized the mean squared error between the estimated compartment 2 concentrations ͑Ĉ 2 ͒ and the experimentally measured concentrations ͑C 2 ͒. 8 For each pair of compart-ments, the subscript 12 was replaced by letters denoting the corresponding compartments with A, C, V, and T denoting arterial ͑breath͒, capillary, venous, and tissue, respectively. For example, k AC is the rate constant, where C 1 is the arterial compartment and C 2 is the capillary compartment.…”
Section: Quantification Of Pharmacokinetic Differencesmentioning
confidence: 99%
“…However, at high concentrations, because of saturation of hepatic enzymes or renal capacity, the elimination process may become zeroorder. For instance, the pharmacokinetics of ethanol is best described by a threecompartment model with zero-and first-order processes taking place simultaneously [15]. Corresponding corrections of the PK model and equations are required in this case (for details, see [11]).…”
Section: Troubleshootingmentioning
confidence: 99%
“…Alcohol is converted to acetate in the periphery, particularly in the liver (6,7), and it is released to the blood (8). Administration of ethanol to humans elevates blood acetate (6, 9, 10) from <0.1 mM to 1 to 2 mM within minutes of the start of the administration (11,12).…”
Section: Introductionmentioning
confidence: 99%